Latent Trade Diversification and Its Relevance for Macroeconomic Stability - Lederman, Daniel; Pienknagura, Samuel; Rojas, Diego (World Bank, Washington, DC, 2015)
Traditional measures of trade diversification only take into account contemporaneous export baskets. These measures fail to capture a country’s ability to respond to shocks by allocating factors of production into activities for which it has already paid the fixed costs associated with exporting. This paper corrects for the shortcoming of traditional measures of diversification by introducing a novel measure of trade diversification—latent diversification—and proposes a proxy to measure latent diversification, which is calculated by taking into account the entire history of a country’s exports. The paper shows that the observed gaps between traditional measures of diversification and the proposed proxy of latent diversification are sizeable; countries hold latent export baskets that are, on average, three times as large as their average contemporaneous export basket, and these gaps are largest for poor and small countries. Moreover, latent diversification is an important determinant of volatility—more diversified latent export baskets are associated with lower terms of trade volatility and, subsequently, lower GDP per capita volatility, even after controlling for the degree of contemporaneous export diversification and other trade and country characteristics. The latter result, together with the disproportionately large latent baskets relative to contemporaneous baskets observed in poor and small countries, suggests that latent diversification is an important vehicle toward stability in countries that face barriers in building diversified contemporaneous export baskets.